The benefits of bidding and hosting the Olympic Games are difficult to justify due to the overall costs - Burgo, E.; Cromartie, F. J. (The Sport Journal, 2018)
In examining the high cost of placing a bid or hosting the Olympic Games, cities face a dilemma. Benefits and risks may not be worth the investments. Data were used from past Olympic successes and failures with the addition of comparable events and outcomes. Tangible and intangible results were considered in establishing benefit justification. Studies find that bidding cities as well as host cities seem to benefit through world recognition; however, the cost is extreme and creates questions about financial risks. Poor countries seem to be apprehensive due to the capital investments involved leaving opportunity for the affluent countries to invest money in infrastructure. The attraction of world-wide attention allows the wealthy countries an opportunity to risk capital with the possibility of stimulating the economy through tourism and trade.